Christology from within : spirituality and the Incarnation in Hans Urs von Balthasar - McIntosh, Mark Allen, 1960- (Studies in spirituality and theology, 1996)
Mark McIntosh’s examination of the unique christological thought of twentieth-century theologian Hans Urs von Balthasar provides a valuable example of how christology and spirituality can come together to offer a more humanistic idea of Christ.